An aromatic cluster in Lysinibacillus sphaericus BinB involved in toxicity and proper in-membrane folding - Chooduang, Sivadatch (2020)
The binary toxin from Lysinibacillus sphaericus has been successfully used for controlling mosquito-transmitted diseases. Based on structural alignments with other toxins, an aromatic cluster in the C-terminal domain of BinB (termed here BC) has been proposed to be important for toxicity. We tested this experimentally using BinB mutants bearing single mutations in this aromatic cluster. Consistent with the hypothesis, two of these mutations, F311A and F315A, were not toxic to Culex quinquefasciatus larvae and were unable to permeabilize liposomes or elicit ion channel activity, in contrast to wild-type BinB. Despite these effects, none of these mutations altered significantly the interaction between the activated forms of the two subunits in solution. These results indicate that these aromatic residues on the C-terminal domain of BinB are critical for toxin insertion in membranes. The latter can be by direct contact of these residues with the membrane surface, or by facilitating the formation a membrane-inserting oligomer.